THE INFLUENCE OF SOLVENT TYPES ON THE DERIVATIZATION PROCESS USING BIS-TRIMETHYLSILYL TRIFLUOROACETAMIDE (BSTFA) ON COMPOUNDS ANALYSIS OF ACID, BASE, AND ALCOHOL AS A CHEMICAL WEAPONS DERIVATES - Pusfitasari, Eka Dian; Andreas, - (LIPI Press, 2013)
The existence of chemical weapon compounds is forbidden, but its use is still possible by illegal activities such as terrorism. If the compounds were used, they will soon unravel. Therefore, we have to go through to thedegradation product to detect those compounds. Almost all degradation products of chemical weapons are polar and non-volatile because they have some functional group called -OH and -NH2. Consequently, the analysis of these compounds cannot be directly determined by using gas chromatography without derivatization step process. The aim of this study was to determine the effect of the solvent used as the medium during the process of derivatization using BSTFA. The solvent themselves consist of fi ve types, namely acetonitrile, n-hexane, dichloromethane, chloroform, and carbon tetrachloride. The using of acetonitrile and hexane as the derivatization process media did not yield consistent results on the ratio of the area of the chromatograms. Meanwhile, dichloromethane, chloroform,and carbon tetrachloride generated good results; although for very low analyte concentrations, carbon tetrachloride provided more consistent and higher intensity than the chromatograms of DCM and CHCl3 solvent media. The optimum condition we met from the derivatization process was heat up to 70 C for 30 minutes with the addition of 50 ?l BSTFA, and the solvent used as the derivatization process medium was CCl4.